4th National Meeting to mark World Oral Health Day in Havana, Cuba - Estela de los Ángeles Gispert Abreu; Ricardo Rodríguez Llanes; Elizardo Alemán Hernández (Editorial Ciencias Médicas, 2018)
Since 2015, every 20 March, the Cuban Society of Stomatology organizes activities at the national level in greeting of the "World Day of Oral Health", promoted by the International Dental Federation since 2013. This year 2018, in its fourth edition, the conceived program reflected cognitive, educational and research aspects oriented to the promotion of a positive vision of oral health under the national motto "Optimists in search of oral health vision." The world motto was "I think in my mouth, I take care of my health"; but in our context we promote the need to think from a health approach that anticipates and creates conditions to preserve the oral health status or restore it in the initial phases in order to avoid aggravation, tooth loss and systemic repercussions. The day was developed with a large participation of professionals and technicians, in which representatives of several provinces were present and the attendance of new professionals of the union became manifest. The scientific program was coordinated by the MCs. Dr. María Rosa Sala Adam. The introductory conference "Vision of positive oral health" was in charge of Dr. Cs. Stomatological Stele of the Angels Gispert Abreu and the MCs. Dr. Jorge Luis Bécquer Águila. In it the lecturers offered a positive overview of oral health; They highlighted that this vision should guide the commitment to action in order for the profession to achieve better results at a social level in all contexts, including in our country where health promotion and the prevention of oral diseases are a priority. The Roundtable "Prevention and Control of Smoking" was then offered by the MCs. Lic. Ana Cepero Gil and the MCs. Dr. Esther Catillo. They began with the declaration of "Smoke Free Event," stating that this statement should prevail in all activities of the health sector. They also reflected the magnitude of the problem in Cuba, the implications of active and passive smoking, as well as the benefits of its prevention and control for the well-being of the population. Mention was made of the role of the health ministries and persuasive communication to prevent smoking and smoking cessation. "Epidemiology" was another round table offered by Dr. Ileana Frómeta and the MSc. Dr. Gilda García in which criteria were presented to tackle the epidemiology of dental caries and chronic immunoinflammatory periodontal diseases, a topic that is of special importance for all health, given the pandemic condition that identifies both conditions with high risk of loss of the dental organs, which affects the quality of life. Then the Round Table "Teaching media," developed by the MCs. Lic. Niovis Pedro Jarro and Dr. Juana Sánchez Peraza, analyzed how to improve their development and alternatives for its application, with the aim of contributing to health education, a task that must be assumed by all the professionals and technologists of Stomatology . Dr. Ana María Blanco Céspedes spoke on health promotion and mentioned the meritorious work of the MCs. Aracelis Rivero López in the circle of interest that he directs in the municipality 10 de Octubre, in which he has achieved that the students identify with the stomatology and appropriate the need for oral health care by means of didactic methods attractive to the age group . In the final considerations, Dr. Bécquer highlighted the massive attendance and participation that enriched the presentations. He also referred to the large turnout of the new generation of stomatologists and technologists of the stomatology, responsible for continuing the path of contributions to the health of the population.